Central Bank Digital Currency Adoption Determinants in Developing Countries: Determinan Adopsi Central Bank Digital Currency di Negara Berkembang - Auliya, Elena; Darmayanti, Novi; Rosyida, Isnaini Anniswati (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid digital transformation of financial systems has accelerated the development of Central Bank Digital Currency (CBDC) as a strategic instrument in modern monetary policy and payment systems. Specific Background: In developing countries such as Indonesia and Nigeria, CBDC adoption varies due to differences in implementation stages, financial ecosystems, and public readiness. Knowledge Gap: Previous studies predominantly focus on technological and macroeconomic determinants, with limited integration of financial literacy, monetary policy accountability, and trust in financial authorities within a unified cross-country model. Aims: This study aims to examine the role of financial literacy, monetary policy accountability, and trust in financial authorities in shaping CBDC adoption using a mixed method approach. Results: The findings reveal that financial literacy and trust exhibit negative and significant relationships with CBDC adoption, reflecting increased public critical awareness of risks, while monetary policy accountability shows a positive and significant relationship. Simultaneously, all variables significantly explain CBDC adoption with high explanatory power (Adjusted R² = 0.962083). Novelty: This study integrates cognitive, institutional, and psychological dimensions in a cross-country analysis, providing a multidimensional perspective on CBDC adoption in developing economies. Implications: The results suggest that CBDC implementation requires comprehensive and adaptive policies emphasizing public trust, transparency, and risk communication beyond technological readiness. Highlights• Financial literacy relates negatively to adoption due to heightened risk awareness• Monetary governance transparency strengthens acceptance of digital currency systems• Trust deficits remain a critical barrier in early-stage implementation contexts KeywordsCentral Bank Digital Currency; Financial Literacy; Monetary Policy Accountability; Trust In Financial Authorities; Developing Countries